2006
DOI: 10.1007/s00431-005-0045-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of newborns with Fetal Growth Restriction (FGR) in weight and/or length based on constitutional growth potential

Abstract: This study was carried out to build statistical models for defining FGR (Fetal Growth Restriction) in weight and/or length after taking growth potential of an infant into account. From a cohort of pregnant women having given birth to 47,733 infants in 141 French maternity units, two statistical models gave individualized limits of birth weight and birth length (based on the 5th centile) below which, after adjustment for its individual growth potential, a newborn must be considered as FGR in weight and/or in le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 24 publications
(33 reference statements)
5
26
0
1
Order By: Relevance
“…Birth weight and length and weight and height at 2 and 4 years are mandatory information in the French health care system and were retrospectively obtained from the individual health book, a record of growth measurements, vaccinations, and significant health-related events for every child in France (19). Weight at birth was converted into percentiles and SD score for age and sex according to the French customized birth weight curves, Association of Users of Computerized Medical Records in Paediactrics, Obstetrics, and Gynaecology (AUDIPOG) (14), which accounted for maternal age, weight before pregnancy, height, parity, gestational age, and sex. Current weight and height and pubertal stage were assessed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Birth weight and length and weight and height at 2 and 4 years are mandatory information in the French health care system and were retrospectively obtained from the individual health book, a record of growth measurements, vaccinations, and significant health-related events for every child in France (19). Weight at birth was converted into percentiles and SD score for age and sex according to the French customized birth weight curves, Association of Users of Computerized Medical Records in Paediactrics, Obstetrics, and Gynaecology (AUDIPOG) (14), which accounted for maternal age, weight before pregnancy, height, parity, gestational age, and sex. Current weight and height and pubertal stage were assessed.…”
Section: Methodsmentioning
confidence: 99%
“…To address these questions, we studied 117 obese children and adolescents divided into three groups according to their fetal growth category as determined with French customized birth weight standards (14), after exclusion of maternal diabetes. They were found to be comparable for age, sex, pubertal stage, and percent body fat assessed by dual-energy X-ray absorptiometry: 32 had HBW according to customized standards (HBWcust), 52 were eutrophic, and 33 had LBW according to customized standards (LBWcust).…”
Section: Diabetes Care 31:1031-1036 2008mentioning
confidence: 99%
See 1 more Smart Citation
“…Their study used two classifications to define growth restriction: 1) a reduction of )20% of the estimated fetal weight from the 22 nd gestational week until birth, based on serial ultrasound scans, and 2) a classification at birth as AGA or SGA using the 10 th percentile of a customized growth chart as a cut-off. Similar to Mamelle et al (2006) w24x, Verkauskiene et al (2007 found AGA babies who were growth restricted and SGA babies who were not growth restricted. In our study, we tried to minimize this difficulty by using a more restricted cut-off to define SGA: birth weight equal to or -2 SD below the mean.…”
Section: Discussionmentioning
confidence: 76%
“…In a study considering constitutional growth potential based on maternal characteristics, Mamelle et al (2006) demonstrated that the group of infants classically classified as SGA was heterogeneous in respect to having suffered in utero growth restriction: some were SGA by weight and/or length but were in fact not growth restricted w24x. Additionally, some infants, classified as AGA by weight and/or length, had suffered growth restriction w24x.…”
Section: Discussionmentioning
confidence: 99%